Effects of Robotic Social Cues on Interpersonal Attributions and Assessments of Robot Interaction Behaviors. (September 2015) - Wiltshire, Travis J.; Lobato, Emilio J. C.; Garcia, David R.; Fiore, Stephen M.; Jentsch, Florian G.; Huang, Wesley H.; Axelrod, Benjamin
We discuss an experiment investigating the influence of social cues expressed by a robot on human attributions of interpersonal characteristics towards a robot and assessments of its interaction behaviors. During a hallway navigation scenario, participants were exposed to varying expressions of proxemic behavior and gaze cues over repeated interactions with a robot. Analysis of participant perceptions of the robot's personality revealed that cues indicative of socially mindful behavior expressed by the robot promote positive interpersonal attributions and perceptions of safe robot behavior. Results of the present study contribute to the scholarly discussion on robotic design for encouraging natural and effective interactions between humans and robots.